Articulations of Resistance : Transformative Practices in Contemporary Arab-American Poetry - Harb, Sirene (New York, NY : Routledge, 2020)
Using a theoretical framework located at the intersection of US ethnic studies, transnational studies, and postcolonial studies, Articulations of Resistance: Transformative Practices in Arab-American Poetry maps an interdisciplinary model of critical inquiry to demonstrate the intimate link and multilayered connections between poetry and resistance. In this study of contemporary Arab-American poetry, Sirne Harb analyzes how resistance, defined as the force challenging the dominant, intervenes in ways of rethinking the local and the global vis--vis traditional paradigms of time, space, language and value.
OCLC-licensed vendor bibliographic record.
Keywords: LITERARY CRITICISM / American / General; LITERARY CRITICISM / Middle Eastern; LITERARY CRITICISM / Poetry; Arab American poetry -- 20th century; American poetry -- Arab American authors